2016
DOI: 10.2118/174553-pa
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Reservoir Applicability of Hydrophobically Associating Polymer

Abstract: In this paper, the reservoir characteristics and fluid properties of a reservoir of the Bohai Sea oil field were taken as the research platform. It was confirmed that there exists compatibility between hydrophobically-associating-polymer (HAP) molecular aggregation and pore-throat size. The experiment for oil displacement in heterogeneous cores indicated that there exists applicability of HAP for a heterogeneous reservoir and the applicability can be influenced by polymer concentration. The experiment for oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(40 citation statements)
references
References 3 publications
0
39
0
1
Order By: Relevance
“…Besio et al reported that the polymers in extended (stretched) form are likely to get adsorbed more than when being in the quiescent coiled state due to a larger size. Further, for the same permeability, RF and residual resistance factor (RRF) increase for AP with the increase in the concentration . The authors attributed the increase in RF and RRF to the increased apparent viscosity caused by the intense association.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Besio et al reported that the polymers in extended (stretched) form are likely to get adsorbed more than when being in the quiescent coiled state due to a larger size. Further, for the same permeability, RF and residual resistance factor (RRF) increase for AP with the increase in the concentration . The authors attributed the increase in RF and RRF to the increased apparent viscosity caused by the intense association.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, the RF of AP and HPAM in the porous media needs a comparative investigation, considering CAC in shear and extensional flow, and thereby, the effect of hydrophobic association onset. Similarly, the stronger the hydrophobic associations, the higher the RRF will be . Thus, considering the nature of hydrophobic association, the extensional role on permeability reduction by AP also requires a comparative investigation with HPAM.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure change value, liquid producing capacity, water rate, and oil rate in each period were recorded, and then the recovery factor was calculated. The experimental process diagram is shown in Figure 8 [14].…”
Section: Methodsmentioning
confidence: 99%
“…However, most of HAPs were applied to improve oil recovery in the petroleum industry . Due to a small amount of hydrophobic groups was grafted at hydrophilic polymer chains, the HAPs possess good solubility and thickening effect . The large hydrophobic groups in the side chain of polymer increased hydrodynamic volume of polymer, leading to the viscosity of solution increased .…”
Section: Introductionmentioning
confidence: 99%